Evaluation of two commercially available chikungunya virus IgM enzyme-linked immunoassays (ELISA) in a setting of concomitant transmission of chikungunya, dengue and Zika viruses. (February 2020) - Kikuti, Mariana; Tauro, Laura B.; Moreira, Patrícia S.S.; Nascimento, Leile Camila J.; Portilho, Moyra M.; Soares, Gúbio C.; Weaver, Scott C.; Reis, Mitermayer G.; Kitron, Uriel; Ribeiro, Guilherme S.
Highlights: Inbios and Euroimmun CHIKV IgM ELISAs had low sensitivities for acute sera, as expected. For convalescent sera, both kits had high sensitivities (>92%). Convalescent sera specificity was 91% for the Inbios and 84% for the Euroimmun kit. The Euroimmun kit may yield more false-positive cases if CHIKV circulation is low. Abstract: Objective: To evaluate the diagnostic performance of the Inbios (Seattle, US) and Euroimmun (Luebeck, Germany) chikungunya virus (CHIKV) IgM enzyme-linked immunoassays (ELISAs). Methods: We evaluated the tests' accuracy on sera from 372 patients enrolled in an acute febrile illness surveillance study performed in Salvador, Brazil from Sept/2014 to Jul/2016, a period of simultaneous CHIKV, dengue (DENV), and Zika (ZIKV) virus transmission. We assessed the sensitivity on acute and paired convalescent sera from RT-PCR-confirmed CHIKV cases (collected at median one and 19 days post-onset of symptoms, respectively), and the specificity on sera of RT-PCR-confirmed DENV and ZIKV cases, and on negative patients. Results: The Inbios and Euroimmun tests' sensitivities for acute samples were 4.0% and 10.3%, while for convalescent samples they were 92.4% and 96.9%, respectively. Overall, Inbios IgM ELISA specificities for acute and convalescent samples were 97.7% and 90.5%, respectively, and Euroimmun specificities were 88.5% and 83.9%, respectively. Conclusions: Both tests presented high sensitivity for convalescent samples. However, the Euroimmun test returned more equivocal results and presented a slightly lower specificity, which might result in a higher rate of false positives if the test is used in scenarios of low CHIKV transmission, when the chance of CHIKV infection is lower.